1994
DOI: 10.1128/iai.62.7.2687-2694.1994
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, enzymatic, and pathogenic studies of the iron superoxide dismutase of Campylobacter jejuni

Abstract: Campylobacter jejuni is a microaerobic bacterium that produces an acute, self-limiting, watery or bloody diarrhea in humans. Little is known about how C. jejuni causes disease or even what specific capabilities it requires for survival in vivo. The enzyme, superoxide dismutase (SOD), which catalyzes the breakdown of superoxide radicals to hydrogen peroxide and dioxygen is one of the bacterial cell's major defense mechanisms against oxidative damage. A PCR-based search for sod genes in C. jejuni 81-176 revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(67 citation statements)
references
References 48 publications
(43 reference statements)
0
67
0
Order By: Relevance
“…In contrast, Campylobacter is not likely to grow outside a host, since it is exposed to thermal, osmotic and oxidative stresses. Iron seems to play an important role in both processes; Campylobacters have developed iron binding and transport systems which allow them to acquire su⁄cient iron for growth [15], whereas iron compounds also function as cofactors for the oxidative stress defense systems allowing aerobic survival [9,10,19,75,76,79]. Furthermore, there may be a link between hemin and enterotoxin activity of C. jejuni [111], although the issue of enterotoxin production by C. jejuni is controversial [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Campylobacter is not likely to grow outside a host, since it is exposed to thermal, osmotic and oxidative stresses. Iron seems to play an important role in both processes; Campylobacters have developed iron binding and transport systems which allow them to acquire su⁄cient iron for growth [15], whereas iron compounds also function as cofactors for the oxidative stress defense systems allowing aerobic survival [9,10,19,75,76,79]. Furthermore, there may be a link between hemin and enterotoxin activity of C. jejuni [111], although the issue of enterotoxin production by C. jejuni is controversial [20].…”
Section: Discussionmentioning
confidence: 99%
“…The SodB protein is located in the cytoplasm, and was characterized in both C. jejuni and C. coli. C. jejuni and C. coli sodB mutants did not exhibit growth retardation in laboratory conditions, but were attenuated in intracellular survival in epithelial cells [75] and in chicken colonization [10]. The C. coli sodB mutant was also severely a¡ected in its survival in milk and on chicken skin, aerobic survival during stationary phase, and interestingly also freeze^thaw stress [10,11].…”
Section: Superoxide Stress Defensementioning
confidence: 99%
See 1 more Smart Citation
“…If the cell is unable to neutralise these toxic compounds, they can lead to protein, nucleic acid and membrane damage. Exposure of Campylobacter to oxygen induces catalase, not superoxide dismutase (SOD), the major defence against oxidative stress in most bacteria (Garenaux et al, 2008), though basal activity of SOD may be important (Pesci et al, 1994). The best described catalase in C. jejuni is encoded for by katA (Cj1385 in C. jejuni NCTC11168) (Day et al, 2000;Atack & Kelly, 2009).…”
Section: Oxygen Tolerance and Survival In Low Nutrient Environmentsmentioning
confidence: 99%
“…H. pylori has a superoxide dismutase (SOD) and sequencing and alignment revealed striking homology to the following facultative intracellular human pathogens : Listeria ivanovii, Listeria monocytogenes, Coxiella burnetii, Porphyromonas gingivalis, Legionella pneumophila and Entamoeba histolytica [71]. The H. pylori SOD gene further resembles a SOD gene found in Campylobacter jejuni and it has been shown that the absence of the SOD gene impairs the ability of C. jejuni to survive within epithelial cells (INT407) (12-fold reduction in viability of intracellular organisms) [72]. A similar mechanism could be suspected in H. pylori.…”
Section: Putative Involvement Of H Pylori Genes In Epithelial Cell Imentioning
confidence: 99%